Azospirillum brasilense inoculation counteracts the induction of nitrate uptake in maize plants. (4th February 2019) - Pii, Youry; Aldrighetti, Anna; Valentinuzzi, Fabio; Mimmo, Tanja; Cesco, Stefano
Abstract : Maize plants inoculated with Azospirillum brasilense show reduced nitrate uptake rates during the induction period but the bacteria may supply the plants with reduced nitrogen in the form of ammonium. Abstract: Nitrogen (N) represents one of the limiting factors for crop growth and productivity and to date has been widely supplied via external application of fertilizers. However, the use of plant growth-promoting rhizobacteria (PGPR) might represent a valuable tool to further improve plant nutrition. This study examines the influence of Azospirillum brasilense strain Cd on nitrate uptake in maize ( Zea mays ) plants, focusing on the high-affinity transport system (HATS). Plants were induced with nitrate (500 µM) and either inoculated or not with Azospirillum . Inoculation decreased the nitrate uptake rate in induced plants, suggesting that Azospirillum may negatively affect HATS in the short term. The expression dynamics of ZmNF-YA and ZmLBD37 suggested that Azospirillum affected the N balance in the plants, most probably by supplying them with reduced N, i.e. NH4 + . This was further corroborated by measurements of total N and the expression of ammonium transporter genes. Overall, our data demonstrate that Azospirillum can counteract the plant response to nitrate induction, albeit without compromising N nutrition. This suggests that the agricultural application of microbial inoculants requires fine-tuning of external fertilizer inputs.